Continuous liquid-phase valorization of bio-ethanol towards bio-butanol over metal modified alumina. (February 2015) - Riittonen, Toni; Eränen, Kari; Mäki-Arvela, Päivi; Shchukarev, Andrey; Rautio, Anne-Riikka; Kordas, Krisztian; Kumar, Narendra; Salmi, Tapio; Mikkola, Jyri-Pekka
Abstract: Commercial mixed-phase aluminum oxide was used as a heterogeneous catalyst support, providing slightly basic properties which are well-suited for the condensation of bio-ethanol to C4 hydrocarbons, such as 1-butanol. Different metals (Cu, Ni and Co), at various metal loadings were deposited on the support. Consequently, the catalytic reactions were carried out in a continuous laboratory-scale fixed bed reactor operated at 240 °C and 70 bar. The catalysts were characterized by means of XRD, TEM, FT-IR, XPS and ICP-OES. Different metals were found to give entirely different product distributions. With the best catalysts, the selectivities towards 1-butanol close to 70% were reached, while the ethanol conversion typically varied between 10 and 30% – strongly depending on the metal applied. It was observed that low loading of copper and high loading of nickel were responsible for the formation of 1-butanol, whereas cobalt and high loading of copper resulted in the production of ethyl acetate. The reaction was found to be extremely sensitive to catalyst preparation conditions and procedures such as metal loading, calcination/reduction temperature and, thereby, to the formation of corresponding crystallite structure. Graphical abstract: Highlights: Ethanol can be converted to 1-butanol with 70% selectivity. Alumina is suitable catalyst support. Crystallite structure key issue in the reaction. Surface aluminates have an impact on product distribution. Cu, Co and Ni are suitable metals.